Administration of Isoproterenol and Adenosine to Guide Supplemental Ablation After Pulmonary Vein Antrum Isolation. (10th September 2013) - ELAYI, CLAUDE S.; DI BIASE, LUIGI; BAI, RONG; BURKHARDT, J. DAVID; MOHANTY, PRASANT; SANTANGELI, PASQUALE; SANCHEZ, JAVIER; HONGO, RICHARD; GALLINGHOUSE, G. JOSEPH; HORTON, RODNEY; BAILEY, SHANE; BEHEIRY, SALWA; et al.
Administration of Isuprel/Adenosine After PulmonaryVein Antrum Isolation: Background: Pulmonary vein antrum isolation (PVAI) remains associated with atrial fibrillation (AF) recurrence. We administered adenosine and isoproterenol (ISP) after PVAI to uncover non‐PV atrial triggers and PV reconnection, potentially increasing ablation success rate. Methods: One hundred and ninety‐two consecutive patients with symptomatic AF presenting for PVAI were prospectively studied (group 1). Following PVAI, adenosine (18–24 mg) and ISP (20–30 mcg/min) were administered intravenously. Supplemental ablation was performed in patients with non‐PV triggers that induced AF (group 1A). Other subgroups included patients with (group 1B) or without (group 1C) consistent non‐PV atrial foci that did not induce AF. A cohort of 196 matched control patients undergoing PVAI without drug challenge was used for comparison (group 2). Results: A total of 132 atrial non‐PV foci were revealed (31 inducing AF). The majority of atrial foci were observed with ISP (113/132, 86%). Less than 5% of patients had persistent PV recovery during the drug challenge. During a mean follow‐up of 22 ± 8 months, PVAI was successful in 110/192 (57%, group 1) versus 100/196 (52%, group 2), P = 0.038. Furthermore, the success rate was statistically different between group 1A (25/32, 78%), group 1B (28/83, 34%), and group 1C (57/74, 74%), P < 0.001. Conclusion: After PVAI, ablation guided by the administration of adenosine and ISP to target non‐PV triggers inducing AF increased AF ablation outcomes. Patients with non‐PV foci that did not induce AF had no further ablation, with the lowest ablation success rate. This group may likely benefit from further ablation after PVAI.